GUARDING THE FUTURE OF MOBILITY: CYBER THREATS AND DEFENSES IN AUTONOMOUS VEHICLES (British Journal of Global Ecology and Sustainable Development, 2025)
Autonomous vehicles (AVs) are transforming mobility with their integration of sensors, artificial intelligence, and interconnectivity. While these systems promise safety, efficiency, and sustainability, they also expose AVs to unprecedented cybersecurity risks. This article reviews major attack vectors—such as GPS spoofing, LiDAR manipulation, in-vehicle network intrusions, and wireless exploits—and highlights defensive strategies including biometric encryption, cryptographic protocols, and AI-based anomaly detection. Human awareness and regulatory oversight remain equally critical to strengthening resilience. The future of AV adoption hinges on layered cybersecurity approaches that safeguard passengers and public trust.